Reckless proliferation and guardianship proliferation: The fast breeder nuclear reactor and the plutonium economy - Madureira, Nuno Luis (Technology and Culture, 2019)
This article examines the history of the fast breeder reactor as a forerunner technology in three Western nuclear nations—the United States, the United Kingdom, and France—to clarify just how this charismatic technology changed the nuclear landscape. Did the adoption of fast reactors tip the nuclear balance toward a plutonium economy? And what were the interconnections between the production of plutonium for nuclear reactors and plutonium for atomic bombs? The conclusions reached differentiate between the decentralized and liberal U.S. plutonium economy from the British and the French state-controlled economies largely serving military interests. This furthermore conveys how the usage of plutonium made criticism of nuclear power both systematic and inclusive by tying together technological, political, and social risks and establishing a common bond between anti-breeder policies and environmental concerns.